A study on the correlation between green bond market, coal market and crude oil market - an empirical analysis based on wavelet coherence - Han, Jiazong (Transactions on Economics, Business and Management Research, 2024)
Achieving carbon peaking and carbon neutrality represents a green industrial revolution with immense and far-reaching significance, and the "dual-carbon" goal plays a crucial role in China's realization of high-quality economic development and comprehensive green transformation of economic and social development. In this paper, the wavelet model is employed to extract dynamic correlation information across different time periods and time scales using wavelet coherence. For the overall and sectoral renewable energy indices for the period of 2014-2024, the results of wavelet coherence show that: short-term dependence between crude oil prices and coal prices, and coal prices and green bond indices is relatively weak, but long-term dependence is gradually strengthened, mainly around 2018. As for crude oil and green bond index, there is an extremely significant positive correlation between the two at any frequency. These findings carry significant implications for China's policy decisions regarding investor support and the development of renewable energy, as well as for the sustainable growth of the carbon market.